A Deletion Involving CD38 and BST1 Results in a Fusion Transcript in a Patient With Autism and Asthma - Ceroni, F; Sagar, A; Simpson, N; Gawthrope, A; Newbury, D; Pinto, D; Francis, S; Tessman, D; Cook, E; Monaco, A; Maestrini, E; Pagnamenta, A; et al. (John Wiley and Sons Inc., 2014)
CD38 encodes a ligand in the oxytocin signaling pathway. Some single nucleotide polymorphisms in this gene have been associated with low serum oxytocin levels in autism spectrum disorder (ASD) patients. Oxytocin disruption has been hypothesized to account for features of ASD, including impaired communication and social behavior, based on animal studies. Recent human studies have shown administration of oxytocin improving emotion recognition, promoting social behavior, and improving auditory processing of social stimuli in ASD patients. In addition to its role in oxytocin signaling, CD38 is involved in the regulation of calcium concentration in airway smooth muscle with impairment of CD38 being implicated in airway diseases like asthma. While a number of studies have implicated rare chromosomal deletions and duplications in helping determine genetic risk for autism, there are to our knowledge no reports describing rearrangements involving CD38 or deletions in patients with ASD. Here, we present two sisters diagnosed with autism and with features of regression-previously acquired speech lost in the second year of life. The younger sister, who also had asthma, inherited a maternal deletion of 4p15.32 that results in a BST1-CD38 fusion transcript. Their mother's deletion was mosaic and she was not affected. Although further work is required to assess functional consequences of the fusion transcript, we hypothesize that the proband's deletion may have served as a risk factor for autism that, when combined with other susceptibility variants, resulted in a more severe presentation than her sister. Autism Res 2014, 7: 254-263. © 2014 International Society for Autism Research, Wiley Periodicals, Inc.